2022
DOI: 10.7150/jca.76719
|View full text |Cite
|
Sign up to set email alerts
|

Therapy-related Acute Lymphoblastic Leukaemia has a Unique Genetic Profile Compared to De Novo Acute Lymphoblastic Leukaemia

Abstract: Background: Unlike therapy-related myeloid neoplasms, therapy-related acute lymphoblastic leukaemia (tr-ALL) is poorly defined due to its rarity. However, increasing reports have demonstrated that tr-ALL is a distinct entity with adverse genetic features and clinical outcomes. Methods: We compared the clinicopathological characteristics and outcomes of patients diagnosed with tr-ALL (n = 9) or de novo ALL (dn-ALL; n = 162) at a single institution from January 2012 to March 2021. The mutational landscapes of ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…Compared to newly diagnosed ALL (dn ALL), the occurrence of high-risk cytogenetic and molecular features is higher in t-ALL. These features include BCR::ABL1 positivity, MLL rearrangements, and hyperdiploid (3,7,11,12). Several studies have also indicated that the incidence of BCR::ABL1 positivity is similar between these two types of leukemia (3,13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to newly diagnosed ALL (dn ALL), the occurrence of high-risk cytogenetic and molecular features is higher in t-ALL. These features include BCR::ABL1 positivity, MLL rearrangements, and hyperdiploid (3,7,11,12). Several studies have also indicated that the incidence of BCR::ABL1 positivity is similar between these two types of leukemia (3,13).…”
Section: Discussionmentioning
confidence: 99%
“…These features include BCR::ABL1 positivity, MLL rearrangements, and hyperdiploid (3,7,11,12). Several studies have also indicated that the incidence of BCR::ABL1 positivity is similar between these two types of leukemia (3,13). The most commonly mutated genes in dn ALL were IKZF1 (37%), CDKN2A (14%), SETD2 (13%), and CDKN2B (11%).…”
Section: Discussionmentioning
confidence: 99%
“…NGS data analysis was carried out using the DxSeq analyzer (Dxome). Single-nucleotide variants, small insertions and deletions, and copy number variants were detected using established methods [ 18 , 19 ]. Variant allele frequency (VAF) represents the proportion of sequence reads that align with a particular DNA variant, divided by the total coverage observed at that specific genomic location.…”
Section: Methodsmentioning
confidence: 99%
“…NGS data analysis was conducted using a DxSeq analyzer (Dxome). Single-nucleotide variants, small insertions and deletions, and copy number variants were identified according to previously described methods ( 18 , 19 ). Confirmation of germline variant was achieved with NGS results using skin fibroblast analysis.…”
Section: Methodsmentioning
confidence: 99%